Acetylcholine receptor binding antibody–associated myasthenia gravis, myocarditis, and rhabdomyolysis induced by tislelizumab in a patient with colon cancer: A case report and literature review - Wang, Shengnan; Peng, Danping; Zhu, Hao; Min, Wanwan; Xue, Mengru; Wu, Rui; Shao, Yanqing; Pan, Lin; Zhu, Mingqin (Frontiers in Oncology, 2022)
Despite the intriguing therapeutic prospects offered by immune checkpoint inhibitors (ICIs), immune-related adverse events (irAEs) become an increasingly important safety issue. Herein, we report a patient with locally advanced colorectal cancer (LACRC) who received anti-programmed cell death protein 1 (PD-1) (tislelizumab) therapy, then developed weakness of the limbs and drooping eyelids. He experienced sequential irAEs including severe myasthenia gravis, myocarditis and rhabdomyolysis. Although many irAEs caused by tislelizumab have been reported, the cooccurrence of severe myasthenia gravis, myocarditis and rhabdomyolysis caused by tislelizumab has not been described. The patient responded well to methylprednisolone and intravenous immunoglobulin therapy. This case illustrates the severe toxicity caused by ICIs, highlighting the importance of early prevention, early diagnosis, and appropriate management of irAEs. Multidisciplinary discussions should be held to improve the prognosis of patients.